How Parents Understand Evaluation Process – Mental Models as the Main Obstacle for Engaging Parents in School Evaluation - Dorczak, Roman; Mazurkiewicz, Grzegorz (International Journal about Parents in Education, 2023)
One of the most important elements ofthe recent reform of the school inspection system in Polandis to focus on the parents’ voice through the collection of data during evaluation process in schools. Three years of experience with this system has shown that there still is a lot of confusion with the actual understanding of the evaluation process among all the groups actively involved: external evaluators (school inspectors), head-teachers, teachers, and representatives of school partners, parents and students. The authors claim that this is the most important obstacle in the promotion of evaluation as a crucial element in the process of school development. The paper presents an attempt to describe different understandings of school evaluation among parents actively partaking in this process which was undertaken randomly in Polish schools of different types. The paper shows how these understandings can influence participation of parents in an external evaluation process, and following developmental activities that take place in schools. The authors claim that an understanding of different ways of thinking about evaluation process through the analysis of the metaphors used by parents can be a good basis for drawing up recommendations for those working on parents’ participation in transforming school reality.